Monetary disunion: The domestic politics of Euroland - Wolfgang Streeck; Lea Elsässer (Max Planck Institute for the Study of Societies, 2014)
Regional disparities within the European Union have always been perceived as an impediment to monetary integration. This is why discussions on a joint currency, from their very beginning, were linked to compensatory payments in the form of regional policy payments. Structural assistance to poor regions and member states increased sharply at the end of the 1980s. Today, however, fiscal support has to be shared with the new member states in the East. Moreover, due to the financial crisis, the cheap credit that poor EMU member countries enjoyed as a result of interest rate convergence is no longer available. We predict that in the future, some sort of financial aid will have to be provided by rich member countries to poor ones, if only to prevent a further increase in economic disparities and related political instability. We also expect long-lasting distributional conflict between payer and recipient countries far beyond current rescue packages, together with disagreement on the extent of aid required and the political control to be conceded by receiving countries to giving countries. We illustrate the dimension of the distributional conflict by comparing income gaps and relative population size between the center and the periphery of Europe on the one hand and on the other, between rich and poor regions in two European nation-states characterized by large regional disparities, Germany and Italy. While income gaps and population structures are similar in the two countries to those between Northern Europe and the Mediterranean periphery, regional redistribution is much more extensive in the two nation-states. We conclude that this presages a difficult future for the domestic politics of Euroland. – – Regionale Disparitäten in der Europäischen Union galten immer als Hindernis für den währungspolitischen Integrationsprozess. Aus diesem Grund waren die Verhandlungen über eine zukünftige Währungsunion von Anfang an mit Forderungen nach Ausgleichszahlungen in Form von regionalpolitischen Hilfsprogrammen verknüpft. Strukturhilfen an arme Regionen und Mitgliedsstaaten wurden Ende der 1980er-Jahre erhöht. Heute müssen die entsprechenden Mittel allerdings mit den neuen Mitgliedsstaaten im Osten geteilt werden. Zudem können die ärmeren EWU-Mitglieder seit der Finanzkrise keine günstigen Kredite mehr aufnehmen. Wir gehen davon aus, dass es auch in Zukunft finanzielle Transfers von den reichen zu den armen Mitgliedsstaaten wird geben müssen, selbst wenn sie nur dazu dienen, stärkere wirtschaftliche Disparitäten und damit einhergehende politische Instabilität zu verhindern. Zudem können über die gegenwärtigen Rettungsmaßnahmen hinaus lang anhaltende zwischenstaatliche Verteilungskonflikte zwischen Geber- und Empfängerländern erwartet werden, in welchen es vor allem um den Umfang der Finanzhilfen und die im Gegenzug verlangte Abgabe politischer Kontrolle durch die Empfänger von Transfers gehen wird. Um die Dimension des Verteilungskonflikts zu veranschaulichen, vergleicht der Aufsatz Einkommenslücken und relative Bevölkerungsgrößen zwischen Peripherie und Zentrum der EU mit denen zwischen armen und reichen Regionen zweier Nationalstaaten mit starken regionalen Disparitäten, Italien und Deutschland. Während Einkommenslücken und Bevölkerungsstruktur in den beiden Nationalstaaten denen innerhalb der EWU ähneln, ist die regionale Umverteilung in den Nationalstaaten weitaus höher. Wir schließen daraus, dass die Innenpolitik der Eurozone konfliktreich sein wird.
Keywords: 300